The Characteristics of Professional Administrators as Opinion by Teachers in the Large Secondary Schools in Mueang Khon Kaen District: คุณลักษณะของผู้บริหารสถานศึกษามืออาชีพตามความคิดเห็น ของครูโรงเรียนมัธยมศึกษาขนาดใหญ่พิเศษ ในเขตอำเภอเมืองขอนแก่น - Pononsa, Pimkamon (Journal of Graduate MCU KhonKaen Campus, 2022)
The purpose of the study to compare the opinion of teachers in the large secondary schools which difference in sex, educational degree and age about the trait of professional administrators in the large secondary schools in Mueang Khon Kaen district. The sample groups of the study were 254 teachers in the large secondary schools in Mueang Khon Kaen district. The instrument used in collecting data was a questionnaire with rating - scale. The statistic used in analyzing data were percentage, means, standard deviation, t-test and F-test Results of the study were the following 1) The characteristics of professional administrators as opinion by teachers in the large secondary schools in Mueang Khon Kaen district were rated at a highest level. 2) The characteristics of professional administrators as opinion by teachers in the large secondary schools in Mueang Khon Kaen district which difference in sex and education degree revealed not statistically significant at the .05 level. 3) The characteristics of professional administrators as opinion by teachers in the large secondary schools in Mueang Khon Kaen district which difference in age all aspects had revealed not statistically significant at the .05 level.